2015
DOI: 10.1152/ajpheart.00519.2015
|View full text |Cite
|
Sign up to set email alerts
|

Rat cardiac troponin T mutation (F72L)-mediated impact on thin filament cooperativity is divergently modulated by α- and β-myosin heavy chain isoforms

Abstract: The primary causal link between disparate effects of human hypertrophic cardiomyopathy (HCM)-related mutations in troponin T (TnT) and α- and β-myosin heavy chain (MHC) isoforms on cardiac contractile phenotype remains poorly understood. Given the divergent impact of α- and β-MHC on the NH2-terminal extension (44-73 residues) of TnT, we tested if the effects of the HCM-linked mutation (TnTF70L) were differentially altered by α- and β-MHC. We hypothesized that the emergence of divergent thin filament cooperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 53 publications
4
30
0
Order By: Relevance
“…Post-hoc t -tests confirmed that TnT R97L had no effect on E D in either α-MHC ( P =0.44; Table 1) or β-MHC fibers ( P =0.54; Table 1). We have previously demonstrated that E D is strongly correlated to maximal tension [13, 25, 32, 36]. Similar observations in E D and maximal tension (Table 1) substantiate our conclusion that TnT R97L does not affect maximal activation regardless of the MHC isoform.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Post-hoc t -tests confirmed that TnT R97L had no effect on E D in either α-MHC ( P =0.44; Table 1) or β-MHC fibers ( P =0.54; Table 1). We have previously demonstrated that E D is strongly correlated to maximal tension [13, 25, 32, 36]. Similar observations in E D and maximal tension (Table 1) substantiate our conclusion that TnT R97L does not affect maximal activation regardless of the MHC isoform.…”
Section: Resultssupporting
confidence: 90%
“…The composition of HR solution is listed in our previous works [11, 13]. Left ventricular (LV) papillary muscle bundles were extracted and further dissected into smaller muscle bundles (~0.15 mm in cross-section and 2.0 mm in length) and chemically-skinned overnight at 4°C in HR solution containing 1% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations